Eating Disorders and their Relation with Emotional Disturbances among Undergraduate Students in Malaysia during COVID-19 Pandemic - Faisal, Ghasak Ghazi; Radeef, Ali Sabri; Ibrahim, Omar (Siriraj Medical Journal, 2023)
Objective: COVID-19 pandemic has greatly impacted several aspects of undergraduate students’ lives including significant effect on mental wellbeing, physical activity and eating habits which might increase the risk for developing eating disorders as these disorders tend to emerge at university age. This study aimed to assess the prevalence of eating disorders and their associated factors among undergraduate students. Materials and Methods: A cross sectional study was conducted among 624 undergraduate students from three different universities in Malaysia. Eating disorders was assessed using the Malay version of the Eating Disorder Examination Questionnaire (EDE-Q) while the emotional disturbances was assessed by the Malay version of Kessler Psychological Distress Scale (K10) and perceived social support was assessed by the revised Malay version of The 8-item Multidimensional Scale of Perceived Social Support (MSPSS). Results: The prevalence of eating disorders among students was 14.9%. There were significant differences in terms of gender and other socio-demographic factors. Eating disorders were significantly associated and positively correlated with emotional disturbances level r = 0.37. While inverse correlation between social support and eating disorders was also shown r= -0.13. Multiple linear regression analysis showed that emotional disturbances level (β = 0.212, P = 0.000) and poor social support (β = -0.126, P = 0.002) were a significantly important risk factor. Conclusion: Eating disorders are prevalent among undergraduate students, female students, emotional disturbances and high BMI are significantly associated factors. Emotional disturbances and poor social support are predictive factor for eating disorders.